PENGARUH KECERDASAN EMOSI, SIKAP MANDIRI, DAN LINGKUNGAN TERHADAP MINAT BERWIRAUSAHA PADA MAHASISWA (Studi Pada Politeknik Bisnis Indonesia) - Asmawati Halilah Damanik; Junaidi Junaidi (Jurnal Ekonomi dan Bisnis (EK dan BI), 2022)
Entrepreneurship is one of the factors that can stimulate the improvement of the Indonesian economy because it can increase people's productivity, stimulate the wheels of the national economy, develop creativity and community abilities, and can also increase foreign exchange and attract foreign investors to invest in Indonesia if entrepreneurship runs smoothly. The government also encourages the birth of young entrepreneurs through the socialization of KUR Goes to Campus. Interest in entrepreneurship can be influenced by several factors including: emotional intelligence, independent attitude and the environment. This study aims to test and prove empirically the influence of emotional intelligence on interest in entrepreneurship, the influence of independent attitude on interest in entrepreneurship, and the influence of the environment on interest in entrepreneurship with the object of research being students of the Politeknik Bisnis Indonesia. The contribution of this research is useful in developing the entrepreneurial spirit among students, increasing interest in entrepreneurship and as an evaluation in entrepreneurship learning. This research is confirmatory and will empirically examine the structural relationship between variables. Methods of data collection using a questionnaire. The object used for the sample in this study were 68 students of the Indonesian Business Polytechnic. Data analysis was carried out using a structural equation model to test the research hypotheses using the SMARTPLS 4 application. Independent attitude and environment have a significant influence on the variable of Entrepreneurial Interest. From this study, the results of the statistical T test on the Emotional Intelligence variable with a value of 0.941, independent attitude with a value of 2.890 and Environment with a value of 23,879 explain that the independent attitude and environment variables have a significant influence on the entrepreneurial interest variable.